2022
DOI: 10.1177/16094069221116972
|View full text |Cite
|
Sign up to set email alerts
|

Using Body-Map Storytelling for Accessing Insights in an Educational Intervention for Food Consciousness

Abstract: Body-map storytelling (BMST) is a qualitative visual research methodology and has been used to access embodied subjective experiences in different areas of knowledge, with few studies in the field of nutrition. The consciousness of body experiences can decrease vulnerability to environmental stimuli for food consumption, which can be advantageous in contemporary changes with a significant appeal to food overconsumption. This study aimed to present the application of the BMST as an integral part of the Food and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…In works already published, it was demonstrated that the PESC was able to increase interoceptive sensitivity (sensitivity to bodily physiological sensations), to promote a greater expression of exteroceptive perception (perception and processing of environmental sensory stimuli) ( Palazzo et al, 2022 ), and to promote reflection on the embodied eating experiences incited by the intervention ( Leghi et al, 2022 ). In this way, the PESC represents an essential step in the search for dietary interventions capable of promoting the perception of bodily sensations triggered by environmental and physiological stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…In works already published, it was demonstrated that the PESC was able to increase interoceptive sensitivity (sensitivity to bodily physiological sensations), to promote a greater expression of exteroceptive perception (perception and processing of environmental sensory stimuli) ( Palazzo et al, 2022 ), and to promote reflection on the embodied eating experiences incited by the intervention ( Leghi et al, 2022 ). In this way, the PESC represents an essential step in the search for dietary interventions capable of promoting the perception of bodily sensations triggered by environmental and physiological stimuli.…”
Section: Introductionmentioning
confidence: 99%